2018
DOI: 10.1590/1414-431x20176472
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes promote cetuximab resistance via the PTEN/Akt pathway in colon cancer cells

Abstract: Cetuximab is widely used in patients with metastatic colon cancer expressing wildtype KRAS. However, acquired drug resistance limits its clinical efficacy. Exosomes are nanosized vesicles secreted by various cell types. Tumor cell-derived exosomes participate in many biological processes, including tumor invasion, metastasis, and drug resistance. In this study, exosomes derived from cetuximab-resistant RKO colon cancer cells induced cetuximab resistance in cetuximab-sensitive Caco-2 cells. Meanwhile, exosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…Tumour-derived EVs have been implicated in resistance to numerous therapeutics by mediating the transfer of specific miRNA and/or protein species from drug-resistant to drug-sensitive cells. This phenomenon has been demonstrated across several cancer types and therapies including Tamoxifen (anti-estrogen) [ 72 ] therapies in breast cancer, Cetuximab (anti-EGFR) therapy in colon cancer [ 73 ] and Pazopanib (chemotherapy) in soft tissue sarcoma [ 74 ]. In these studies, exposure to EVs from resistant cells was demonstrated to disrupt drug-associated signalling pathways in sensitive recipients, and this is proposed to contribute to the development of resistance.…”
Section: Evs As Cancer Biomarkersmentioning
confidence: 99%
“…Tumour-derived EVs have been implicated in resistance to numerous therapeutics by mediating the transfer of specific miRNA and/or protein species from drug-resistant to drug-sensitive cells. This phenomenon has been demonstrated across several cancer types and therapies including Tamoxifen (anti-estrogen) [ 72 ] therapies in breast cancer, Cetuximab (anti-EGFR) therapy in colon cancer [ 73 ] and Pazopanib (chemotherapy) in soft tissue sarcoma [ 74 ]. In these studies, exposure to EVs from resistant cells was demonstrated to disrupt drug-associated signalling pathways in sensitive recipients, and this is proposed to contribute to the development of resistance.…”
Section: Evs As Cancer Biomarkersmentioning
confidence: 99%
“…Multiple studies across several systemic cancers have shown that EV-mediated transfer of functional cargo (mRNAs, miRNAs, long non-coding RNA (lncRNA), and proteins) induces drug resistance in drugsensitive cancer cells [76] . The transferred functional molecules upsurge drug efflux [77][78][79][80] , enhance drug metabolism/inactivation [81] , activate anti-apoptotic and tumor-promoting pathways [82][83][84][85][86][87][88] , elicit downstream changes in signal transduction and gene expression [89][90][91][92][93][94][95] , and promote epithelial-to-mesenchymal transition [96][97][98][99] to favor a resistant phenotype. GBM cells actively modulate the composition of EVs in response to chemotherapy and radiation [100,101] .…”
Section: Gbm-mediated Ev Transfermentioning
confidence: 99%
“…In contrast to their use as immune‐stimulators, tEVs are also capable of aiding tumor in the circumvention of immunotherapies. Cetuximab is a recombinant epidermal growth factor receptor monoclonal antibody that is now used clinically in the treatment of several cancers . It may be used as a therapeutic agent in addition to other chemotherapy drugs for example, irinocetan, for some patients with metastatic CRC and previously was shown to improve clinical outcomes of CRC patients with wild‐type KRAS.…”
Section: Crc Tevs In Immunotherapeuticsmentioning
confidence: 99%
“…However, a subset of patients with wild‐type KRAS still derives no benefit from Cetuximab treatment and acquired drug resistance limits its utility. A recent study has reported that Cetuximab‐resistant CRC cells are capable of inducing resistance in Cetuximab‐sensitive cells, and that this effect is mediated by tEVs . This suggests that targeting of tEVs could be beneficial in preventing drug resistance in the future.…”
Section: Crc Tevs In Immunotherapeuticsmentioning
confidence: 99%